***RETRACTED***HUBUNGAN ANTARA HYGIENE SANITASI DENGAN JUMLAH COLIFORM AIR MINUM PADA DEPOT AIR MINUM ISI ULANG (DAMIU) DI KABUPATEN DEMAK TAHUN 2012 (Unnes Journal of Public Health, 2014)
RETRACTION TO: Mirza, M.N. 2014. HUBUNGAN ANTARA HYGIENE SANITASI DENGAN JUMLAH COLIFORM AIR MINUM PADA DEPOT AIR MINUM ISI ULANG (DAMIU) DI KABUPATEN DEMAK TAHUN 2012. Unnes Journal of Public Health, 3(2). This article has been retracted by Publisher based on the following reason: It is reported that this article has been published in KEMAS: Jurnal Kesehatan Masyarakat Volume 9 Issue 2, 2014 [https://journal.unnes.ac.id/nju/index.php/kemas/article/view/2845]. Unnes Journal of Public Health and KEMAS: Jurnal Kesehatan Masyarakat are sister journals in the same institution. It was miscoordination that the both journals published a same student article. Unnes Journal of Public Health takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.